Commodity Price Volatility and the Sources of Growth. (10th September 2014) - De V. Cavalcanti, Tiago V.; Mohaddes, Kamiar; Raissi, Mehdi
Summary This paper studies the impact of the growth and volatility of commodity terms of trade (CToT) on economic growth, total factor productivity, physical capital accumulation and human capital acquisition. We use the standard system generalized methods of moments (GMM) approach as well as the dynamic common correlated effects pooled mean group (CCEPMG) methodology for estimation to account for cross‐country heterogeneity, cross‐sectional dependence and feedback effects. Using both annual data for 1970–2007 and 5‐year non‐overlapping observations, we find that while CToT growth enhances real output per capita, CToT volatility exerts a negative impact on economic growth operating mainly through lower accumulation of physical and human capital. Productivity, however, is not affected by either the growth or the volatility of CToT. Our results also indicate that the negative growth effects of CToT volatility offset the positive impact of commodity booms. Therefore, we argue that volatility, rather than abundance per se, drives the 'resource curse' paradox. Copyright © 2014 John Wiley & Sons, Ltd.